Exploring Effective Knowledge Management Strategies for Achieving Organizational Success - Olasinbo Abiola (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
Successful knowledge management methods are the focus of this research. This research analyzes the efficacy of various knowledge management strategies and the variables that affect their success. The results show that knowledge management practices succeed when they have strong leadership backing, employee buy-in, an attitude of sharing information, a solid technological foundation, and an open and collaborative organizational culture. The research shows that better employee engagement, productivity, innovation, customer satisfaction, and financial outcomes can be achieved by fostering a culture of knowledge sharing, ensuring the backing of leadership, promoting employee participation, and capitalizing on technological infrastructure. Organizations that want to succeed in the long run should look to this research for guidance on how to enhance their knowledge management practices.